Hmong Older Adults' Perceptions of Insider and Outsider Researchers: Does It Matter for Research Participation?. Issue 3 (May 2018) - Lor, Maichou; Bowers, Barbara J.
Abstract : Background: Recruiting racial/ethnic minorities into health research is challenging. Although researchers affiliated with members of the study population (seen as insiders) may increase research participation of racial/ethnic minorities, little is known about who participants see as insiders and how they respond to insider versus outsider researchers. Objectives: The aim of the study was to examine perceptions of Hmong older adults toward insider versus outsider researchers and the influence of these perceptions on their willingness to participate in research. Methods: Participants in a study evaluating use of a culturally and linguistically adapted audio computer-assisted self-interviewing system with helper assistance (ACASI-H) provided information about what they thought would encourage others in their community to participate in research. ACASI-H was used for collection of health data with 30 Hmong older adults. Participants rated the likelihood of participation if the researcher was Hmong and answered open-ended questions about participation when the researcher was not Hmong. Conventional content analysis was used to analyze open-ended questions. Results: Sixteen (53%) participants reported that they would be "likely" to participate in the research if the researcher was Hmong. Fourteen (47%) participants reported that they would participate in research if the researcher was not Hmong. In addition to ethnic affiliation, trust in the researcher could shift the perception of the researcher toward insider status, thereby increasing willingness of Hmong adults to participate in research. Trust in the researcher and movement toward insider status could be increased by calling out a connection between the researcher and the participant or creating reciprocity. Discussion: Findings suggest that increasing research participation of Hmong (and possibly other) participants, particularly when researchers do not share ethnic membership, can be achieved by building trust. This study also suggests a more nuanced perception of insider status, as a continuum, rather than a dichotomy, may be a more accurate reflection of the relationship between participants and researchers.